Antitumor and antimetastatic effects of walnut oil in esophageal adenocarcinoma cells - ŞAHİN, ALİ; YILMAZ GÖLER, AYŞE MİNE; KARTAL ÖZER, NESRİN; BATIREL, SAİME (CHURCHILL LIVINGSTONE, 2018)
Background: Walnuts contain many components including specific fatty acids, which could be active against cancer. Even though the anticarcinogenic effect of some of the individual fatty acids in walnut oil has been described, the effect of walnut oil itself on esophageal cancer cells hasn't yet been investigated. Objective: We aimed to investigate whether walnut oil affects tumor growth and metastatic potential in esophageal cancer cells. Methods: The human esophageal adenocarcinoma cell line, OE19, was treated with different doses of walnut oil and cell viability, apoptosis/necrosis and cell cycle analyses were performed using WST-1 assay and flow cytometry respectively. Adhesion, colony formation and wound healing assays were performed to assess the antimetastatic effects of walnut oil. NFkB expression was evaluated with western blot analysis. Results: Walnut oil decreased the cell viability of esophageal cancer cells in a dose-dependent manner. 20 mg/mL walnut oil reduced cell viability by similar to 50% when compared with control. The analysis revealed that necrosis and accumulation of cells in G0/G1 phase was induced in the cells treated with high doses of walnut oil. It also down-regulated the protein levels of NFkB. Walnut oil suppressed the adhesion, migration and colony formation of the cells. Conclusions: High-dose short-term administration of walnut oil reduces the cell viability and metastatic ability of esophageal cancer cells, while exhibiting anticarcinogenic effect by inducing necrosis and cell cycle arrest at the G0/G1 phase, probably through suppression of the NFkB pathway. These data indicate that walnut oil, and by extension walnut consumption, may have beneficial effects in esophageal cancer in humans. This should be tested by clinical trials in the future. (C) 2017 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: Esophageal cancer; Walnut oil; Antitumor; Antimetastatic; ALPHA-LINOLENIC ACID; CANCER GROWTH; FATTY-ACIDS; PREVENTION; RISK; INHIBITION; MECHANISMS; MICE; DIET